Proximal Femur Guided Growth for the Management of Hip Dysplasia in Children with Cerebral Palsy - Davids, Jon (Journal of the Pediatric Orthopaedic Society of North America, 2021)
Proximal femoral deformity associated with neuromuscular hip dysplasia in children with cerebral palsy (CP) is characterized by increased anteversion, coxa valga, and caput valgum. Guided growth of the proximal femur (PFGG) utilizes a screw to tether the medial portion of the physis to achieve progressive varus alignment of the femoral head and neck with subsequent growth. This procedure has been shown to decrease the head shaft angle and Reimer’s migration percentage (RMP); and decrease the need for subsequent skeletal hip reconstructive surgery. The indications, surgical technique, post-operative management, potential pitfalls of this relatively new procedure are reviewed.